Effect of the tax burden on the activities of business entities (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
The formation of a fundamentally different model of interaction between government and businessentities in the field of taxation has determined the necessity for consideration of the tax component inthe total economic strategy of the enterprises. In this regard there is a need in the formation of individualtax policies of business entities, covering issues of optimization of tax burden. However, despite theparticular relevance of the research question the effect of the value of the tax burden on business entities,this issue found its solution only in the form of general conclusions, calling for increased activity inthe reform of the tax system.At the same time despite the fact that in many works of domestic authors there is the mention of theterm “tax burden of the business entity”, its content is not disclosed in full. Moreover, authors of numerouspublications on tax issues, not made a comprehensive assessment of the enterprises response to thedynamics of the ratio of the tax burden. But, along with other factors that affect the process of formationof a tax policy of the enterprise, the amount of the tax burden plays a significant role in the adoption ofthe economic entity solutions in the field of taxation. Thus, a need arises to research a range of outstandingissues related to the management of economic entities in the sphere of tax relations.